Influência do manuseio neonatal sobre parâmetros comportamentais, bioquímicos e moleculares após o uso de drogas psicoestimulantes em ratos - Antoniazzi, Caren Tatiane de David (2016)
The abusive use of psychostimulant drugs is a common social problem in countries of different cultures, with increasing and alarming incidence, whose discontinuance of use is associated with anxiety and depression cases. Studies have shown the influence of early exposure to stress on patterns of dependency, which can play an important role on the vulnerability to drug abuse in adulthood. On the other hand, procedures such as neonatal tactile stimulation (TS) and neonatal isolation (NI), have been described by interfering with behavioral and neurophysiological parameters that can persist into adulthood. Thus, we first investigated the influence of neonatal handling on conditioned place preference (CPP) induced by amphetamine (AMPH), as well as anxiety-like symptoms and oxidative status related to drug abstinence, in young rats. Male pups of Wistar rats were submitted to TS or NI, for 10 min, from postnatal day 1 (PND1) to 21, while the CPP with AMPH or vehicle (NaCl 0.9% i.p.) was initiated on PND40. AMPH-conditioning evoked drug-preference and abstinence-symptoms in unhandled animals, accompanied by oxidative damage in cortex, hippocampus and striatum, while TS favored a decrease on drug-preference, showing no abstinence symptoms, as observed by reduced anxiety-like symptoms. Oxidative status pointed to a neuroprotective influence of TS by reducing lipid and protein damage in cortex, hippocampus and striatum, and increasing antioxidant markers in blood. Secondly, we aimed to identify the neonatal period in which TS exerts greater influence on animals’ development. Male pups of Wistar rats were submitted to TS (10 min) from PND1 to 7, PND8 to 14 or PND15 to 21. In adulthood, the animals were assessed using behavioral, biochemical and molecular analysis. According to these parameters, it was observed that the animals handled between PND8 and 14 had lower anxiety index, better working memory and increased ability to cope with adverse situations. TS in the second week of pups' lives was capable of reduce plasma corticosterone levels and improve the oxidative status of animals, observed by the slightest damage to lipids, and increased catalase activity in the hippocampus. In addition, TS from PND8 to 14 increased brain derived neurotrophic factor (BDNF) in the hippocampus of animals, while glucocorticoid receptors were reduced in all handling periods, except on PND8 to 14, in the same brain area. Considering the correlation between psychostimulants use and depression-like symptoms, in the 3rd study, the antidepressant effects of TS in association with a subtherapeutic dose of sertraline were evaluated during cocaine withdrawal period. Male pups of Wistar rats were submitted to TS (10 min) from PND8 to 14. For 14 consecutive days, adolescent rats received 3 daily doses of cocaine or vehicle (0.9% NaCl ip). Seven days after cocaine withdrawal, animals received 0.3 mg/kg of sertraline and 30 min later were evaluated for depression- and anxiety-like symptoms. Brain oxidative status and dopamine (D2) and glucocorticoid receptors (GR) were also determined. TS was able to protect animals against the depression-like symptoms, demonstrated by the absence of anhedonia and increased swimming activity in the forced swimming test. TS animals had lower levels of anxiety and stress, as well as reduction of oxidative damage in 8 plasma and brain of animals, besides best response of plasma antioxidant defense system. The molecular analysis also showed that TS was able to alters D2 and GR immunocontent in the striatum and hippocampus of animals. In summary, TS modified AMPH-induced preference, reducing anxiety-like behaviors that are common during drug withdrawal. Moreover, TS is able to stimulate the antioxidant defense system, and protect brain areas closely related to addiction, in young rats. Besides, it was possible to demonstrate that TS may be more effective when applied during the intermediate phase of neonatal development, reflecting reduced emotionality and improved ability to deal with stressful situations later in life. Finally, it was also possible to show that TS in association with sertraline is able to prevent against the deleterious effects of cocaine withdrawal, such as depression and anxiety.